Advances and Barriers in Understanding Presynaptic N-Methyl-D-Aspartate Receptors in Spinal Pain Processing - Dedek, Annemarie; Hildebrand, Michael E. (Frontiers in Molecular Neuroscience, 2022)
For decades, N-methyl-D-aspartate (NMDA) receptors have been known to play a critical role in the modulation of both acute and chronic pain. Of particular interest are NMDA receptors expressed in the superficial dorsal horn (SDH) of the spinal cord, which houses the nociceptive processing circuits of the spinal cord. In the SDH, NMDA receptors undergo potentiation and increases in the trafficking of receptors to the synapse, both of which contribute to increases in excitability and plastic increases in nociceptive output from the SDH to the brain. Research efforts have primarily focused on postsynaptic NMDA receptors, despite findings that presynaptic NMDA receptors can undergo similar plastic changes to their postsynaptic counterparts. Recent technological advances have been pivotal in the discovery of mechanisms of plastic changes in presynaptic NMDA receptors within the SDH. Here, we highlight these recent advances in the understanding of presynaptic NMDA receptor physiology and their modulation in models of chronic pain. We discuss the role of specific NMDA receptor subunits in presynaptic membranes of nociceptive afferents and local SDH interneurons, including their modulation across pain modalities. Furthermore, we discuss how barriers such as lack of sex-inclusive research and differences in neurodevelopmental timepoints have complicated investigations into the roles of NMDA receptors in pathological pain states. A more complete understanding of presynaptic NMDA receptor function and modulation across pain states is needed to shed light on potential new therapeutic treatments for chronic pain.